2004
DOI: 10.1074/jbc.m402875200
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Induces Protein Kinase C-mediated Activation Loop Phosphorylation and Nuclear Redistribution of Protein Kinase D

Abstract: Oxidative stress has been implicated in aging and in a wide range of diseases affecting the nervous, respiratory, cardiovascular, and gastrointestinal systems in humans (1, 2). Exposure of cells to reactive oxygen species (ROS) 1 at high concentrations or for extended periods damages cellular DNA, widely hypothesized to either induce cell death via apoptosis/necrosis (3) or facilitate progression toward malignant transformation (4). In contrast, cell exposure to ROS for brief times and/or at limited concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
61
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(69 citation statements)
references
References 49 publications
6
61
0
2
Order By: Relevance
“…3A). The pattern of PKD translocation in EC is similar to that was observed in Swiss 3T3 cells in response to H 2 O 2 (26). In contrast, TNF did not induce these translocations of PKD (Fig.…”
Section: H 2 O 2 But Not Tnf Induces Cytoplasmic Translocation Of supporting
confidence: 56%
“…3A). The pattern of PKD translocation in EC is similar to that was observed in Swiss 3T3 cells in response to H 2 O 2 (26). In contrast, TNF did not induce these translocations of PKD (Fig.…”
Section: H 2 O 2 But Not Tnf Induces Cytoplasmic Translocation Of supporting
confidence: 56%
“…In this study, we found that pervanadate resulted in phosphorylation of CREB. Previous studies by others showed that oxidative stress induced by H 2 O 2 activates PKD via a PKC-and Src-dependent pathway and results in the nuclear transport of PKD (78,79). Moreover, as H 2 O 2 can induce phosphorylation of CREB in several cell lines (34), this may suggest a possible role of PKD as a CREB kinase in response to oxidative stress.…”
Section: Occurs In Vitro But Not In Vivomentioning
confidence: 83%
“…However, in contrast to JNK, Akt is believed to play a protective role against ROS-induced apoptosis, and pharmacological or genetic inhibition of Akt has been shown to sensitize cells to H 2 O 2 -induced apoptosis (17,32). The activation of PKC has also been shown to occur in response to treatment with H 2 O 2 or chemicals that generate ROS, such as menadione, to cells (13,18,57). In some cases, PKC activation plays a protective role (33): in RALA255 cells (a hepatocyte cell line), PKC inhibitors were found to sensitize cells to ROS-induced apoptosis (58).…”
mentioning
confidence: 99%